MO025ADVANCED GLYCATION END PRODUCTS (AGES) AND SOLUBLE RECEPTOR FOR AGES (SRAGE): ASSOCIATION WITH RISK OF MORTALITY IN CHRONIC KIDNEY DISEASE PATIENTS. (6th June 2020) - Dozio, Elena; Caldiroli, Lara; Nerini, Silvia; Vianello, Elena; Ambrogi, Federico; Messa, Piergiorgio; Corsi Romanelli, Massimiliano Marco; Vettoretti, Simone
Abstract: Background and Aims: In chronic kidney disease patients (CKD), excessive oxidative stress, uremia and chronic inflammation may increase the production of advanced glycation end-products (AGEs) which in turn promote CKD-related morbidities and mortality. Much attention has recently been paid to the soluble receptor for AGEs (sRAGE), as a marker of inflammation, oxidative stress, atherosclerosis and heart failure. sRAGE is a decoy receptor that prevents AGEs binding to RAGE, the cell membrane form of the receptor, and RAGE-related detrimental effects. Both AGEs and sRAGE accumulate in CKD due to the increased production and reduced kidney filtration. Recently, we reported an association between higher levels of sRAGE and mortality in hemodialysis and peritoneal dialysis patients. Whether AGEs, sRAGE and its different isoforms, namely the membrane-cleaved receptor cRAGE and the endogenous secretory form esRAGE, may also work as prognostic factors for mortality in non-dialysis CKD patients is not known. Method: We quantified plasma sRAGE and esRAGE levels in 111 CKD patients (mean±SD age: 77.71±10.24 years, eGFR: 24.86±11.06 ml/min, male gender: 74.86%) by ELISA. Florescent AGEs and glycated albumin (GA) were quantified by AGEs-specific fluorescence (excitation: 365 nm, emission: 414-445 nm) and the quantILab assay (Werfen, Italy), respectively. The cRAGE form was estimated by subtracting esRAGE from sRAGE and the ratio cRAGE/esRAGE was calculated. AGEs were normalized against total proteins. Patients were screened for malnutrition and malnutrition-inflammation score (MIS) was calculated (4-8: risk of malnutrition, >8: malnutrition). The Cox proportional-hazards model was used for investigating the association between variables and survival time. Median follow-up time was 40 months. Results: Mean levels of sRAGE, esRAGE and cRAGE were 2317±1224 pg/ml, 648±453 pg/ml and 1669±901 pg/ml, respectively. The mean value of cRAGE/esRAGE ratio was 2.82±0.96. AGEs/total protein content was 433.2 A.U., GA was 21.3±7.5 % and MIS 5.98 ±4.67. During the follow up, 28 patients died. Univariate Cox regression indicated a prognostic role for mortality for age (HR: 1.100, 95%CI: 1.041-1.163, p < 0.001), AGEs/total protein (HR: 1.004, 95%CI: 1.000-1.007, p < 0.05), esRAGE (HR: 1.001, 95%CI: 1.041-1.001, p < 0.01), cRAGE/esRAGE (HR: 0.5390, 95%CI: 0.331-0.888, p < 0.05) and MIS (HR: 1.079, 95%CI: 1.025-1.137, p < 0.01). After adjusting for age and MIS, the associations were still significant for esRAGE (HR: 1.001, 95%CI: 1.0002-1.001, p < 0.01) and cRAGE/esRAGE ratio (HR: 0.572, 95%CI: 0.347-0.943, p < 0.05), with AGEs/total protein at the margin of statistical significance (HR: 1.004, 95%CI: 0.9997-1.007, p = 0.0726). Conclusion: In CKD higher levels of esRAGE and lower cRAGE/esRAGE ratio may have a prognostic role for mortality. Since esRAGE acts as a decoy receptor for AGEs and thus has a cytoprotective effect, from a pathological point of view the observed association with esRAGE but not cRAGE was quite surprisingly. One potential explanation is that AGEs increases all sRAGE isoforms, but esRAGE accumulation was greater than that of cRAGE due to a different synthesis/catabolism that needs further investigations. In conclusion, in CKD patients esRAGE and cRAGE/esRAGE seem to be useful supportive tools to identify high risk patients.